The Abu Sayyaf group and kidnapping for ransom in Sabah, Malaysia, 2000–2023 - Ramli Dollah; Marja Azlima Omar; Hafiza Nur Adeen Nor Ahmad; Adi Jafar; Nelson Dino (Universiti Utara Malaysia Press, 2025)
Since the formation of the Federation of Malaysia in 1963, the country has faced various traditional security threats. These include the Philippines’ territorial claim over Sabah since 1968 and the Indonesia-Malaysia Confrontation from 1963 to 1966. However, with the evolving nature of global security, the discourse has expanded to include the non-traditional security threats (NTS). One of Malaysia’s key national security concerns is the prevalence of cross-border crimes, particularly along the maritime borders of Sabah’s east coast. Since 2000, the Malaysian government has implemented security policies to combat kidnapping for ransom (KFR). However, the on-going conflict in the southern Philippines has further complicated the security landscape in the region. This study investigates the role of the Abu Sayyaf Group (ASG) in KFR activities from 2020 to 2023. It argues that two primary factors have contributed to the persistence of the KFR: (i) on-going violence in the southern Philippines and (ii) the lucrative nature of the crime. This study employs a qualitative methodology, utilizing data from interviews with key informants, fieldwork observations, official documents from local authorities, and secondary sources. The findings highlight the growing prominence of NTS as a critical national security concern for Malaysia. Specifically, the study reveals that KFR has gained precedence over traditional security concerns, making it a top priority in Malaysia’s national security agenda.